Subjective and Objective Measurements of the Facial Effects of Microdoses of Botulinum Toxin - Hexsel, Doris; Valente-Bezerra, Indira; Mosena, Gabriela; Mourao, Maria Antonia Oakim; Fabris, Vitor Costa (Dermatology Practical & Conceptual, 2023)
Introduction: Studies have suggested that botulinum toxin A may improve skin quality, and application protocols using hyper-diluted doses of botulinum toxin (microdosing) have been studied as a way to achieve therapeutic goals without fully paralyzing the targeted muscles. Objectives: To evaluate the effects of a combined protocol utilizing both the standard dosing and the microdosing of AbobotulinumtoxinA for the improvement of skin quality, measured by objective and subjective measurements. Methods: Thirty patients were treated with botulinum toxin using both the standard technique and the microdosing technique. Objective (Sebumeter®, Mexameter® and digital dermoscopy pictures) and subjective (Global Aesthetic Improvement Scale and a clinical scale for evaluating the quality of facial skin) measurements of the effects in the treated areas were taken to assess the efficacy of the treatment. Results: Digital dermoscopy showed a marked reduction of erythema and telangiectasias. Erythema and telangiectasias improved both on objective and subjective measurements. Skin oleosity, static rhytids, papules and pustules and enlarged pores improved on subjective measurements. Patient satisfaction was high (93%) despite the high rate of adverse events (56%). Conclusions: The combined application of standard doses and microdoses of AbobotulinumtoxinA is effective in improving the overall quality of facial skin. The effects on erythema and telangiectasias suggest that it is an effective treatment option for patients with erythematotelangiectatic rosacea. When applying microdoses of botulinum toxin in the lower and mid-face, the doses and pattern of injection should be customized for each patient to reduce the occurrence of adverse events.